(3TQM GdHQgGfjIs - (3CHh YHO Gddg eMeO Hf CMeO Hf YHO Gddg GdCfUGQj GdCTHjdi GdNUGas ((3CMeO Hf eMeO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ENJQY GdeMOKGJ HbOQJg hCXgQ GdehLhOGJ GdMGOKGJ HEjLGOg hNUUgG HChbGJgG s
(3BNQgG (B:s
(3agPg YbjOI Cgd GdJhMjO GdeNQLI HaVd Gddg JYGdi ef XdeGJ GdLgd hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds